An examination of the basic principles and guidelines for the protection of civilians under international humanitarian law (2016)
International Humanitarian Law (IHL) or the law of armed conflict is the law that regúlales the conduct of armed conjlicts. IHL classifies armed conflict as International armed conflict (IAC) or Non-International armed conflict (NIAC). The dichotomy between the two has over the years become an important threshold question in the determination of which set of rules sliould be applied during armed conflict either within a country or between two belligerent States. International Humanitarian Law is inspired by the consideration of humanity and the mitigation of human suffering during an armed conflict. Due to this consideration, several principies were developed to protect civilian and non-military objects during such armed conflict. Examination of these principies and rules is the focus of this paper. The objective is to consider the adequacy or otherwise of these principies with a view to offering suggestions for improvement.